Profile of the combination of two oral anti-diabetes drugs in patients diabetes melitus at Citra Husada hospital Jember - Miatuz Zaqia; Mayasari, Shinta; Nafisah Isnawati (Sean Institute, 2024)
Diabetes melitus (DM) is a group of diseases with characteristic hyperglycemia that occurs due to impaired insulin secretion, insulin action, or both. The International Diabetes Federation (IDF) notes that Indonesia has the country with the fifth most significant number of diabetics in the world, with 19.5 million Indonesians aged 20-79 years suffering from the disease. Therefore this study aims to determine the profile of the use of a combination of two classes of oral hypoglycemic drugs in type 2 DM patients at Citra Husada Hospital in 2022. This research is a descriptive study with retrospective data collection. The population in this study were all outpatients diagnosed with Type 2 DM at Citra Husada Hospital in 2022. Source of medical record data. The number of samples using a population of 100 patients in the outpatient installation at Citra Husada Hospital. This study used a total sampling technique which is a sampling technique that uses all members of the population. Data analysis used univariate analysis in the form of proportions. Research results show that 100 samples are included in the inclusion criteria. Results of the study Most of the patient characteristics were female (61%), age range 56-65 years (39%), and hypertension co-morbidities (33%). The results of a combination study of two classes of oral anti-diabetes drugs, namely the sulfonylurea group (glimepiride at a dose of 3 mg, the drug frequency is taken once a day every morning with the thiazolidinedione group (pioglitazone at a dose of 30 mg, the drug frequency is taken once a day during the day) (35%). The most common used of combinations of two classes of oral anti-diabetes drugs in patients Diabetes melitus at Citra Husada Hospital are sulfonylureas and thiazolidinediones